Understanding the Role of Immigrants' Legal Status: Evidence from Policy Experiments - Francesco Fasani (Centre for Research & Analysis of Migration (CReAM), Department of Economics, University College London, 2014)
Programs aimed at reducing the presence of unauthorised immigrants are often at the core of the migration policy debate in host countries. In recent years, a growing body of empirical literature has attempted to understand the effect of lacking legal status on immigrants' outcomes and behaviour. The main difficulties in this field are the scarcity of data and the identification challenge posed by endogenous selection into legal status. The vast majority of these articles have therefore used amnesty programs (or similar policy changes) to establish causal relationships. In this paper, we propose a first systematic review of the empirical literature for the US and Europe on the impact of legal status on different immigrants' outcomes. We then present some new evidence of the relationship between labour market outcomes and legal status in the Italian context. In our empirical analysis, we first provide some descriptive evidence on differences in the outcomes for groups with different residence statuses, and we then exploit a specific amnesty programme to produce causal estimates of the impact of legal status. Our results confirm previous findings in the literature and show that the design of the specific amnesty analysed matters in shaping its effects.
Keywords: F22; J61; K37; 330; illegal migration; amnesty; migration policy